Protection from unfair competition on the pharmaceutical market in the conditions of the COVID-19 pandemic - A.O. Kodynets; O.F. Doroshenko; I.P. Volynets; G.K. Dorozhko; V.O. Petrenko; V.V. Belitsky (Medičnì Perspektivi, 2022)
The article reveals the problems and prospects of combating dishonest advertising of medicinal products in the conditions of the COVID-19 pandemic. Using the example of the USA and Ukraine, the criteria for banning the advertising of medicinal products by researching scientific sources, international and domestic legal acts, prescriptions and instructions of state bodies, etc. were analyzed. The differences and specifics of the regulatory requirements for the advertising of medicinal products in Ukraine and the USA have been determined. It has been established that in the USA it is allowed to advertise prescription drugs, and in Ukraine a ban has been introduced to advertise "antiviral drugs of direct action". Attention was drawn to the qualification of the division of advertising slogans in the USA, which made it possible to draw an analogy with Ukrainian advertising of medicinal products. It has been proven that individual pharmaceutical manufacturers, by providing advertisers with incomplete information about the drug, can mislead consumers about its effectiveness. The Antimonopoly Committee of Ukraine has demonstrated cases of countering the spread of false information about the properties of medicinal products, which became more frequent in connection with the emergence of the strain (SARS-CoV-2) in 2019. The advantages and disadvantages of a complete ban on medicines on television and radio, as well as other mass media are indicated in connection with the entry into force of the decision of the National Security and Defense Council of Ukraine "On the state of the national health care system and urgent measures to ensure the protection of citizens of Ukraine with medical assistance" dated July 30, 2021. As an alternative to the complete rejection of drug advertising it is proposed, the introduction of the mechanism of "corrective advertising", which is actively used in the USA and consists in correcting or making amendments to already published drug advertising and eliminating statements that mislead consumers, contain incomplete, inaccurate, false information about the medicinal product.